2022
DOI: 10.3389/fneur.2022.1029010
|View full text |Cite
|
Sign up to set email alerts
|

Predictive value of neutrophil to lymphocyte ratio for ischemic stroke in patients with atrial fibrillation: A meta-analysis

Abstract: ObjectiveAtrial fibrillation (AF) is an important risk factor for stroke, but the currently used CHA2DS2-VASc score has significant limitations in predicting the risk of stroke. It is important to find new biomarkers to predict stroke risk in patients with AF or as a complement to the CHA2DS2-VASc score. Neutrophil-to-lymphocyte ratio (NLR) may be of potential value. This systematic review and meta-analysis evaluated the association between NLR and stroke risk.MethodsWe searched in electronic databases such as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…This finding is supported by current evidence published in the literature, which highlights increased neutrophil extravasation in the atria of AF patients, in addition to observing significant colocalization between enzymes such as myeloperoxidase and areas of atrial myocardial fibrosis [77][78][79]. On the other hand, the neutrophil-lymphocyte ratio has been shown to perform favorably in predicting de novo AF, as well as relevant clinical outcomes such as stroke [80][81][82]. Our results extend these findings across the spectrum of AF, highlighting the activity of the innate immune system as a preserved process of potentially great importance in the development and persistence of this arrhythmia.…”
Section: Discussionsupporting
confidence: 80%
“…This finding is supported by current evidence published in the literature, which highlights increased neutrophil extravasation in the atria of AF patients, in addition to observing significant colocalization between enzymes such as myeloperoxidase and areas of atrial myocardial fibrosis [77][78][79]. On the other hand, the neutrophil-lymphocyte ratio has been shown to perform favorably in predicting de novo AF, as well as relevant clinical outcomes such as stroke [80][81][82]. Our results extend these findings across the spectrum of AF, highlighting the activity of the innate immune system as a preserved process of potentially great importance in the development and persistence of this arrhythmia.…”
Section: Discussionsupporting
confidence: 80%
“…Plasma C1q concentrations in AF patients were considerably lower than in the controls, and in persistent AF, were lower than in paroxysmal AF [ 10 ]. NLR may be regarded as a supplemental risk evaluation tool, particularly for AF patients with a -VASc score below two, because the likelihood of a stroke in AF patients with NLR 3 was 1.4 times greater than in those with an NLR 3 [ 12 ]. The present study found no significant difference in C1q or NLR between the two groups owing to an upregulation in the systemic inflammation in HCM patients.…”
Section: Discussionmentioning
confidence: 99%
“…A larger load of atrial myopathy and fibrosis in HCM patients is believed to hinder sinus impulse propagation across the atrium, thereby providing a substrate for delayed conduction and intra-atrial re-entry [ 8 , 9 ]. As the pathogenesis of AF involves inflammation, serum inflammatory markers, such as complement (C1q), albumin-to-globulin ratio (AGR), and neutrophil-to-lymphocyte ratio (NLR) may be beneficial for the identification and risk stratification of AF [ 10 , 11 , 12 , 13 , 14 ]. However, whether a link exists between the AGR and AF occurrence in HCM patients remains unclear.…”
Section: Introductionmentioning
confidence: 99%